Correlations of exergy destruction during combustion for internal combustion engines. (1st January 2015) - Caton, Jerald A.
The greatest destruction of exergy for internal combustion engines is a result of the combustion process. The fundamental sub–processes which contribute to the combustion irreversibility include mixing, heat transfer and chemical reactions. This work used an engine cycle simulation to provide quantitative connections between the exergy destruction, and eight engine operating and design parameters. For the conditions examined, the exergy destruction during combustion ranged between 20% and 26% of the fuel exergy. For six engine parameters, a correlation with a high coefficient of determination (r2 = 0.99) is obtained between the exergy destruction during combustion and the average ratio of specific heats during combustion. This correlation includes the gas temperature dependence since the ratio of specific heats is proportional to temperature.